Friction measurement and correction method in quasi-static tests of columns under combined axial and cyclic lateral loading. Issue 12 (September 2019) - Wang, Zeyuan; Feng, Peng; Cheng, Shi; Yu, Tao
In quasi-static tests of large-scale structural columns and/or columns under large axial loads, the lateral friction force between the column and the loading system can become a significant problem: they may cause considerable deviation between the measured lateral force and the actual reaction force of the column, especially under large axial compression load. Many researchers have come up with different methods to reduce or eliminate the influence of such friction force. In this article, previous treatments on the lateral friction force in quasi-static tests are first discussed. A shear force measurement device, for accurate measurement of the friction force, is then presented and calibrated. Based on the friction forces measured by the device in real tests, a simple model is proposed to predict the lateral friction force in quasi-static tests. Using the model, the measured lateral force in such tests can be corrected to obtain the actual reaction force of the column when a friction measurement device is absent. The proposed model and the correction method are then validated using results from several previous tests.